Effect of creatine and ß-alanine supplementation on performance and endocrine responses in strength/power athletes - Hoffman, J.; Ratamess, N. A.; Kang, J.; Mangine, G.; Faigenbaum, A.; Stout, J. (International Journal of Sport Nutrition and Exercise Metabolism, 2006)
The effects of creatine and creatine plus ß-alanine on strength, power, body composition, and endocrine changes were examined during a 10-wk resistance training program in collegiate football players. Thirty-three male subjects were randomly assigned to either a placebo (P), creatine (C), or creatine plus ß-alanine (CA) group. During each testing session subjects were assessed for strength (maximum bench press and squat), power (Wingate anaerobic power test, 20-jump test), and body composition. Resting blood samples were analyzed for total testosterone, cortisol, growth hormone, IGF-1, and sex hormone binding globulin. Changes in lean body mass and percent body fat were greater (P < 0.05) in CA compared to C or P. Significantly greater strength improvements were seen in CA and C compared to P. Resting testosterone concentrations were elevated in C, however, no other significant endocrine changes were noted. Results of this study demonstrate the efficacy of creatine and creatine plus ß-alanine on strength performance. Creatine plus ß-alanine supplementation appeared to have the greatest effect on lean tissue accruement and body fat composition.